Extensive vegetative lesions as a side effect of the treatment of severe acne with systemic isotretinoin - Jankowska-Konsur, Alina; Maj, Joanna; Baran, Eugeniusz (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Acne vulgaris is a common disorder affecting adolescents and young adults. Severe acne has a strong negative impact on physical and psychological quality of life and requires intensive treatment. Systemic isotretinoin is an efficient agent in the therapy of severe acne, but it is associated with a wide spectrum of side-effects. Objective . Presentation of atypical skin lesions resulting of the treatment with oral isotretinoin. Case report . The patient, a 21-year-old man, was admitted to the Department of Dermatology with extensive, vegetative lesions covered by thick crusts localized in the submandibular areas, on the upper arms, on the chest and the upper part of the back. The patient has been on systemic isotretinoin for 9 months. The first lesions appeared two months after the initiation of therapy; however, the patient continued the treatment till a week before hospitalization. On the ward, after exclusion of other dermatological and general disorders, oral erythromycin and topical treatment was introduced and the lesions started to recede. Conclusions . Skin lesions are the most common side-effect of systemic isotretinoin therapy. In the world-wide literature no similar vegetative and extensive lesions have been reported. The presented lesions developed most likely due to fragility of the skin and prolonged, uncontrolled treatment. Additional infection with S. aureus could have stimulated massive inflammation.